DYNAMICITY OF INTERLANGUAGE ERRORS: A CASE STUDY OF INDONESIAN STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Fauziati, Endang (Indonesian Journal of Applied Linguistics, 2011)
ABSTRACT: Interlanguage errors are an inevitable sign of human fallibility; therefore, they always exist in foreign language learning. They are very significant since they become the source for studying the system of the learners’ second language (interlanguage). As a language system, interlanguage has at least three prominent characteristics, namely, systematicity, permeability, and fossilization. Applied linguistic researchers are no longer in disagreement with the view that interlanguage is systematic and permeable. However, the premise that interlanguage is fossilized is still debatable. This study deals with interlanguage errors; in particular, this tries to investigate whether the learners’ grammatical errors are fossilized (in a sense that they are dynamic) or static. For this purpose, an empirical study was conducted, using an error treatment method. This study used Indonesian senior high school students learning English as the research subjects. The data were collected from the students’ free compositions written prior and after an error treatment. The error treatment was carried out for one semester. The data were analyzed using quantitative and qualitative method. The result indicates that the learners’ grammatical errors were dynamic. At a certain period of the learning course, some grammatical errors emerged. As a result of the error treatment, some errors were fluctuating; some became stabilized; while others were destabilized. The fluctuating errors tended to be destabilized while the stabilized errors were also likely to be destabilized. Error treatment was proved to have significant contribution to the destabilization process; that is to say, it helped develop the learners’ IL system. A conclusion drawn from this study is that the learners’ grammatical errors are dynamic. They are destabilzable. Thus, there is a possibility for the learners to acquire complete target language grammar. Key Words: error treatment, stabilization, fossilization, dynamicity, interlanguage